2020
DOI: 10.13189/ujer.2020.080749
|View full text |Cite
|
Sign up to set email alerts
|

Concrete-Pictorial-Abstract Approach on Student's Motivation and Problem Solving Performance in Algebra

Abstract: This study aims to: 1) find out whether problem-solving performance in students who are subjected to the CPA approach is better than problem-solving performance in students who are subjected to conventional approaches, 2) find out whether learning motivation in students who are subjected to the CPA approach is better than learning motivation in students who are subjected to conventional approaches. The study was conducted on 7th-grade junior high school students in Purworejo Regency. This study was an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Manipulatives can be used to introduce, practice and remediate concepts [2,12,28]. Research by psychologists Jean Piaget and Jerome Bruner has shown that children master concepts better when their thinking progresses through three hierarchical levels -the inactive (concrete), iconic (pictorial) and the symbolic (abstract) [5,26,27]. Manipulatives represent knowledge at the concrete level where learners can handle and manipulate objects to internalize mathematical processes and procedures.…”
Section: Role Of Manipulativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulatives can be used to introduce, practice and remediate concepts [2,12,28]. Research by psychologists Jean Piaget and Jerome Bruner has shown that children master concepts better when their thinking progresses through three hierarchical levels -the inactive (concrete), iconic (pictorial) and the symbolic (abstract) [5,26,27]. Manipulatives represent knowledge at the concrete level where learners can handle and manipulate objects to internalize mathematical processes and procedures.…”
Section: Role Of Manipulativesmentioning
confidence: 99%
“…Ms Dikgomo seemed to get trapped in the simplistic use of manipulatives. Manipulatives were used at the concrete level only; instead of taking learners through the Concrete-Pictorial-Abstract (C-P-A) levels of representation [27,43]. She then demonstrated how fractions were added stressing the importance of a common denominator, after which learners were given work to do.…”
Section: Use Of Manipulatives In Mathematics Laboratoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying motivation, some researchers pay attention to the importance of the increase in the number of innovations dedicated to implementation of new technological tools (software) which make it possible to enhance pedagogical opportunities of mathematical disciplines teaching [2,3]. Scientists highlight the fact that conventional teaching decreases motivation of students, who become more inactive as compared to the teaching using IC technologies.…”
Section: Introductionmentioning
confidence: 99%